Pre-Service English Teachers’ Attitude Towards Hots to Prepare Better Assessment - Siregar, Renol Aprico (JEELS (Journal of English Education and Linguistics Studies), 2019)
Although Higher-Order Thinking Skill (HOTS) has currently been an ongoing topic of interest among educational researchers, there has been no wide exploration of such notion and its relation to the learning assessment. This instrumental case study aimed to investigate attitudes of Indonesian pre-service English teachers with reference to using HOTS-based test to prepare better assessment. The study was qualitatively conducted to scrutinize the participants’ attitudes on using the HOTS framework in designing more qualified assessment for students. The data were obtained through interview and questionnaire. The total of 10 preservice teachers participating in the study were purposively chosen regarding their familiarity and comprehension with the study issue. The data were analyzed by employing descriptive qualitative data analysis. The result indicated that in spite of some situational restrictions, all of the participants shared their positive attitude towards HOTS principles to be adopted in providing better assessment from the affective, behavioral and cognitive points of view due to some influencing factors. More researches on the area of HOTS and its implementation on the area of assessment were also expected to furnish more contributive information in this issue.